2003
DOI: 10.1002/jcp.10378
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor‐β induces expression of vascular endothelial growth factor in human retinal pigment epithelial cells: Involvement of mitogen‐activated protein kinases

Abstract: Vascular endothelial growth factor (VEGF) is a major agent in choroidal and retinal neovascularization, events associated with age-related macular degeneration (AMD) and diabetic retinopathy. Retinal pigment epithelium (RPE), strategically located between retina and choroid, plays a critical role in retinal disorders. We have examined the effects of various growth factors on the expression and secretion of VEGF by human retinal pigment epithelial cell cultures (HRPE). RT-PCR analyses revealed the presence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
131
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 148 publications
(143 citation statements)
references
References 64 publications
8
131
4
Order By: Relevance
“…Our experimental results seem different from a recent study, using HRPE cells, in which BMP-4 did not affect VEGF secretion [Nagineni et al, 2003]. It is possible that the ARPE-19 cells used in our study have different gene expression than the HRPE cells in that study.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our experimental results seem different from a recent study, using HRPE cells, in which BMP-4 did not affect VEGF secretion [Nagineni et al, 2003]. It is possible that the ARPE-19 cells used in our study have different gene expression than the HRPE cells in that study.…”
Section: Discussioncontrasting
confidence: 99%
“…It is possible that the ARPE-19 cells used in our study have different gene expression than the HRPE cells in that study. In addition, 10 ng/ml of BMP-4 was used in our study, as compared with a higher concentration of 40 ng/ ml used in the reported study [Nagineni et al, 2003]. Furthermore, in our study, BMP-4 treatment of ARPE-19 cells shows significant time-and dosedependency of VEGF secretion (Figs.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Several studies have reported the ability of VEGF to induce TGF-␤1 mRNA expression both in healing tendon and in tendon fibroblasts in vitro (Zhang et al, 2003;Wang et al, 2005). Alternatively, TGF-␤s have also been demonstrated to induce VEGF secretion in cultures of human retinal pigment epithelial cells (Nagineni et al, 2003). TGF-␤s are known to induce expression of fibronectin, which is involved in angiogenesis (Balza et al, 1988;Nicosia et al, 1993).…”
Section: Discussionmentioning
confidence: 99%